2015
DOI: 10.3758/s13421-015-0544-0
|View full text |Cite
|
Sign up to set email alerts
|

Recall is not necessary for verbal sequence learning

Abstract: The question of whether overt recall of to-be-remembered material accelerates learning is important in a wide range of real-world learning settings. In the case of verbal sequence learning, previous research has proposed that recall either is necessary for verbal sequence learning (Cohen & Johansson Journal of Verbal Learning and Verbal Behavior, 6, 139–143, 1967; Cunningham, Healy, & Williams Journal of Experimental Psychology: Learning, Memory, and Cognition, 10, 575–597, 1984), or at least contributes signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Learning in the Hebb repetition task is further considered to depend on implicit learning mechanisms (although explicit awareness often naturally evolves across the repetitions) (Guerard, Saint-Aubin, Boucher, & Tremblay, 2011). For instance, neither explicit awareness of the repeating sequence, nor explicit reproduction of the sequence (i.e., overt recall) during the recall phase, nor focal hippocampal lesions, seem necessarily to affect learning (Couture & Tremblay, 2006;Gagnon, Bedard, & Turcotte, 2005;Gagnon, Foster, Turcotte, & Jongenelis, 2004;Guerard et al, 2011;Kalm & Norris, 2016).…”
mentioning
confidence: 99%
“…Learning in the Hebb repetition task is further considered to depend on implicit learning mechanisms (although explicit awareness often naturally evolves across the repetitions) (Guerard, Saint-Aubin, Boucher, & Tremblay, 2011). For instance, neither explicit awareness of the repeating sequence, nor explicit reproduction of the sequence (i.e., overt recall) during the recall phase, nor focal hippocampal lesions, seem necessarily to affect learning (Couture & Tremblay, 2006;Gagnon, Bedard, & Turcotte, 2005;Gagnon, Foster, Turcotte, & Jongenelis, 2004;Guerard et al, 2011;Kalm & Norris, 2016).…”
mentioning
confidence: 99%
“…Backward serial recall is a variant of the typical serial-recall task in which participants are asked to recall the items in reverse order, from the last presented item to the first presented item. Backward recall allowed us to manipulate overt production order instead of production opportunity (see Cohen & Johansson, 1967;Kalm & Norris, 2016). Indeed, in previous experiments involving trials without a recall requirement, the mechanisms involved in those trials were unclear; retrieval of the items and the production process might already have been activated by the time the participants were instructed not to recall the list.…”
mentioning
confidence: 99%
“…In effect, whereas verbal learning implies the formation of associations between an ordered set of phonemes and a higherlevel representation that has no a-priori relation, typical experiments on the Hebb repetition effect involved stimuli with well-established long-term associations. For example, most experiments using the Hebb repetition task used digits (Cumming, Page, & Norris, 2003;Oberauer & Meyer, 2009), letters (Cunningham et al, 1984;Kalm & Norris, 2016), words (Page et al, 2006;Page et al, 2013), or pictures of well-known objects (Mosse & Jarrold, 2008) as stimuli. Moreover, although language learning implies the auditory perception and a verbal production of words, most studies departed from the natural context of language learning by using visually presented sequences (Saint-Aubin, Guérard, Fiset, & Losier, 2015;Szmalec et al, 2009) or written recall (Hitch et al, 2009;Oberauer & Meyer, 2009;Page et al, 2013).…”
mentioning
confidence: 99%
“…Recently, the Hebb repetition effect has experienced renewed interest as a possible candidate mechanism that enables the transfer of short-term memories (STM) for phonemic sequences into long-term memory (LTM) as words (e.g. Cumming, Page, & Norris, 2003;Kalm & Norris, 2016;Mosse & Jarrold, 2008;Norris, Page, & Hall, 2018;Page, Cumming, Norris, McNeil, & Hitch, 2013;Smalle et al, 2016;Szmalec, Duyck, Vandierendonck, Mata, & Page, 2009;Szmalec, Loncke, Page, & Duyck, 2011;Szmalec, Page, & Duyck, 2012). It has been suggested that following repeated presentation of the Hebb sequence, the items therein form a unified 'chunk' within memory (Page & Norris, 2009) and that this is analogous to how a sequence of phonemes combine to become a word within LTM.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that repeated encoding alone is sufficient to produce the Hebb repetition effect (although their findings also suggest an additive effect of repeated retrieval). Moreover, Kalm and Norris (2016) argued that the use of a strict serialrecall scoring protocol underestimated learning of the sequence. They used the Levenshtein (1966) scoring metric (rather than testing absolute positional recall accuracy) to assess string similarity between the presented sequence and the outputted sequence.…”
Section: Introductionmentioning
confidence: 99%